Electrical Characterization of Individual Cesium Lead Halide Perovskite Nanowires Using Conductive AFM. Issue 12 (17th February 2020) - Stern, Avigail; Aharon, Sigalit; Binyamin, Tal; Karmi, Abeer; Rotem, Dvir; Etgar, Lioz; Porath, Danny
Abstract: Perovskite nanostructures have attracted much attention in recent years due to their suitability for a variety of applications such as photovoltaics, light‐emitting diodes (LEDs), nanometer‐size lasing, and more. These uses rely on the conductive properties of these nanostructures. However, electrical characterization of individual, thin perovskite nanowires has not yet been reported. Here, conductive atomic force microscopy characterization of individual cesium lead halide nanowires is presented. Clear differences are observed in the conductivity of nanowires containing only bromide and nanowires containing a mixture of bromide and iodide. The differences are attributed to a higher density of crystalline defects, deeper trap states, and higher inherent conductivity for nanowires with mixed bromide–iodide content. Abstract : Perovskite nanowires hold great interest due to their interesting physical properties and high potential for use in various photovoltaic and optoelectronic devices. The conductivity of individual cesium lead halide nanowires with two different halide contents is characterized. The conductive properties indicate a higher density of crystalline defects in nanowires containing bromide and iodide relative to nanowires with only bromide.